SEMARE: SEHAT BERSAMA REMPAH UNTUK REVITALISASI GAYA HIDUP ALAMI REMAJA - Hastutik, Hastutik; Wigunantiningsih, Ana (LPPM POLBITRADA, 2026)
Adolescents are an age group vulnerable to the influence of modern, unhealthy lifestyles, such as fast food consumption, high-sugar drinks, and low physical activity. This condition has the potential to reduce adolescent health in the long term. Indonesia is rich in spices that have the potential to be used as an alternative to support a healthy lifestyle based on natural ingredients. This community service activity aims to increase adolescent knowledge and awareness about the benefits of spices as an effort to revitalize a natural lifestyle. The activity was held on January 13, 2026, at SMK Penda 3 Jatipuro, Karanganyar, involving 66 students. The methods used were lectures, discussions, and questions and answers, with leaflets as a medium for education. The results of the activity showed that all participants had consumed herbal medicine and showed a high interest in using spices to treat various minor health problems, such as itchy skin, menstrual pain, acne, and blood sugar management. The ongoing discussion showed an increase in participants' understanding of the benefits, safety, and limitations of spice use. This activity had a positive impact in the form of increased knowledge, enthusiasm, and motivation of adolescents to adopt a healthy lifestyle based on natural ingredients. Education on the use of spices has the potential to be an effective promotional and preventive strategy while also supporting the preservation of local wisdom among adolescents.